Revitalisasi Pemanfaatan Youtube Sebagai Media Pembelajaran Bahasa Indonesia Di UINSU - Nisa Hafzhiyah Hasibuan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The purpose of this research is to reveal the need for updating teaching media. The teaching media used must be close to students' daily lives, such as social media, especially YouTube. Studying and chatting casually with family often uses social media. The era of globalization and social media technology in modern society. The research method used is a qualitative research method, because what is researched is clearer if it is carried out in the observation process. The data sources in this research are videos on YouTube resulting from Indonesian language lesson assignments and interviews conducted by students. It is hoped that the application of social media, such as YouTube, can overcome student boredom by presenting learning material in a more creative and interesting way. This digital era reflects society's transformation towards a more modern daily life, and the habit of using social media indirectly helps users to access and learn information quickly. This explains why the development and spread of language is currently taking place very quickly.